PELABELAN PRIME CORDIAL PADA BEBERAPA GRAF YANG TERKAIT DENGAN GRAF SIKEL - Hapsari, Nindita Yuda; Utomo, Robertus Heri Soelistyo; Ratnasari, Lucia (MATEMATIKA, 2015)
Prime cordial labeling of a graph is a bijective mapping of the set vertex to the set where is the number of vertex . The edge labeling induced the vertex labeling, which is obtained by finding the great common divisor (gcd) of the label of vertex which it’s adjacent. If gcd of the adjacent vertex label is 1 then the label of edge is 1, but if gcd of the adjacent vertex label value other than 1 then the label of edge is 0, and the absolute value of the difference between the number of edges labeled 0 and the number of edges labeled 1 is less than equal with 1. A graph admits prime cordial labeling is called prime cordial graph. In this paper, we study about edge duplication cycle graph (except for ), vertex duplication cycle graph , path union union of cycle the graph and friendship graph one point union of copies of cycle .